Implementasi Algoritma Greedy dan Midtrans pada Sistem Informasi Pelatihan K3 Berbasis Web - Alvin Alvin; Vina Ayumi (Riau Jurnal Teknik Informatika, 2026)
Occupational Safety and Health (OSH) is an essential aspect of creating a safe and productive working environment. PT Marka Katiga Diklatama, which manages 15 OSH training programs with an average of 25 participants per month, still performs part of its training management and payment verification processes manually, resulting in inefficiency. This study aims to develop a web-based OSH training information system using the Waterfall method and the CodeIgniter 4 framework. The system integrates the Midtrans payment gateway to automate payment verification and implements the Greedy algorithm to determine the most popular training programs based on the number of registered participants. The results show that the system is capable of managing registration, payment, and reporting processes more effectively while automatically generating rankings of the most popular training programs. Based on User Acceptance Testing (UAT) involving 34 respondents, the system achieved an acceptance rate of 87.14%, which falls into the highly feasible category. The developed system supports more efficient management of OSH training services and facilitates the company's decision-making process.